Experimental study on the CHF enhancement effect of nanofluids on the oxidized low carbon steel surface. (5th March 2022) - Wang, Laishun; Ye, Weijie; He, Xiaoqiang; Wu, Shuai; Ming, Pingjian; Wang, Jun; Cheng, Hui; Yan, Binghuo
Highlights: CHF in distilled water increases rapidly with boiling time and then reaches a limit. CHF in nanofluids is independent of boiling time and still higher than that of oxidized surface. Surface wettability increases and nucleation site decreases is the key of CHF enhancement. Abstract: Studies about using nanofluids to enhance the Critical Heat Flux (CHF) of In-vessel Retention (IVR) strategy in the third-generation reactor have been conducted extensively and show a significant CHF enhancement effect. However, low carbon steel SA508 used in the reactor vessel is easy to oxidize and the oxidation can lead to changes in the surface properties which may affect the CHF enhancement effect of nanofluids. In this study, pool boiling CHF experiments with low carbon steel SA508 surfaces were conducted in distilled water and nanofluids under different boiling time to investigate the CHF enhancement effect of nanofluids under low carbon steel surface oxidization condition. CHF in distilled water increases rapidly with boiling time due to the rapid surface oxidation during the boiling and the increase ratio can be nearly 2 due to the surface oxidation. CHF in nanofluids is stable and independent of boiling time. The difference between CHF in nanofluids and CHF in distilled water decrease to 17% under the longest boiling time conditions due to the surface oxidation. The deposition layer of nanoparticles on the surface leads to the capillary wicking and decrease in the nucleation site and thus, CHF is enhanced. This study is of great significance for exploring the actual effect of nanofluids on the CHF enhancement of IVR strategy.